Face and content validity of variables associated with the difficult-to-sedate child in the paediatric intensive care unit: A survey of paediatric critical care clinicians. Issue 3 (May 2018) - Lebet, Ruth M.; Asaro, Lisa A.; Zuppa, Athena F.; Curley, Martha A.Q.
Abstract: Background: Clinicians recognise that some critically ill children are difficult-to-sedate. It may be possible to identify this clinical phenotype for sedation response using statistical modelling techniques adopted from machine learning. This requires identification of a finite number of variables to include in the statistical model. Objective: To establish face and content validity for 17 candidate variables identified in the international literature as characteristic of the difficult-to-sedate child phenotype. Methods: Paediatric critical care clinicians rated the relevance of 17 variables characterising the difficult-to-sedate child using a four-point scale ranging from not (1) to highly relevant (4). Face and content validity of these variables were assessed by calculating a mean score for each item and computing an item-level content validity index. Items with a mean score >1 were rated as having adequate face validity. An item-level content validity index ≥0.70 indicated good to excellent content validity. Setting and participants: Web-based survey emailed to members of the Pediatric Acute Lung Injury and Sepsis Investigators Network or the Society of Critical Care Medicine Pediatric Sedation Study Group. Results: Of 411 possible respondents, 121 useable surveys were returned for a response rate of 29%. All items had a mean score >1, indicating adequate face validity. Ten of 17 items scored an item-level content validity index ≥0.70. The highest scoring items were requiring three or more sedation classes simultaneously, daily modal sedation score indicating agitation, sedation score indicating agitation for 2 consecutive hours, receiving sedatives at a dose >90th percentile of the usual starting dose, and receiving intermittent paralytic doses for sedation. Conclusions: Computation of an item-level content validity index validated variables to include in statistical modelling of the difficult-to-sedate phenotype. The results indicate consensus among paediatric critical care clinicians that the majority of candidate variables identified through literature review are characteristic of the difficult-to-sedate child.